Pengaruh Brand Equity Terhadap Keputusan Pembelian Mie Instan Merek Indomie (Studi Pada Mahasiswa Perguruan Tinggi di Kabupaten Kendal) - Kurniawan, Bayu; Sutrisno, Sutrisno; Damayanti, Lenny (FEB Universitas Sam Ratulangi Manado, 2020)
This study aims to determine the effect of brand awareness, brand associations, perceived quality and brand loyalty partially and simultaneously on the decision to purchase Indomie brand instant noodles for college students in Kendal Regency. Data collection was carried out by distributing questionnaires. Data analysis in this study is quantitative data analysis. Sampling using purposive sampling technique. The samples obtained were 107 respondents. The analytical tool in this study using IBM SPSS version 23. The data analysis method used is multiple regression analysis. The results showed that partially the Brand Awareness variable had a positive effect on purchasing decisions, seen from the t count of 4.556> t table 1.983 with sig. smaller than 0.05, which is 0.000. The Brand Associations variable has a positive effect on purchasing decisions, seen from the t count of 2.292> t table of 1.983 with sig. smaller than 0.05, namely 0.024. Perceived Quality variable has a positive effect on purchasing decisions, seen from the t count of 4.255> t table 1.983 with sig. smaller than 0.05, which is 0.000. Brand Loyalty variable has a positive effect on purchasing decisions, seen from the t count of 4.214> t table 1.983 with sig. smaller than 0.05, which is 0.000. Simultaneously, the variables of brand awareness, brand associations, perceived quality and brand loyalty together have a significant effect on purchasing decisions, seen from the calculated F value of 25.628> F table 2.46 with sig. smaller than 0.05, which is 0.000. Meanwhile, the coefficient of determination (R2) of 0.631 means that the contribution of independent variables (brand awareness, brand associations, perceived quality and brand loyalty) affects the dependent variable (purchase decision) by 63.1%, while the remaining 36.9% is influenced by other variables in beyond the research model. The conclusion from this study is that it is proven that brand awareness, brand associations, perceived quality and brand loyalty have a partial and simultaneous effect on purchasing decisions, so it can be explained that the better brand awareness, brand associations, perceived quality and brand loyalty, the higher the decision to buy noodles. instant brand Indomie for College Students in Kendal Regency.